Bone marrow or adipose tissue mesenchymal stem cells: Comparison of the therapeutic potentials in mice model of acute liver failure. Issue 7 (25th March 2018) - Zare, Hossein; Jamshidi, Shahram; Dehghan, Mohammad M.; Saheli, Mona; Piryaei, Abbas
Abstract: Acute liver failure (ALF) is a lethal disease with limited life‐saving therapy. Because lack of whole organ donors for liver transplantation, a substitute treatment strategy is needed for these patients. Preclinical and clinical findings have proved that treatment with mesenchymal stem cells (MSCs) is beneficial for recovery from ALF. In this approach, however, the appropriate sources of these cells are unclear. In the present study, we investigated and compared the therapeutic potentials of bone marrow‐mesenchymal stem cells (BM‐MSC) with those of adipose tissue (AT‐MSC) in carbon tetrachloride (CCL4)‐induced acute liver failure in mice. Murine BM‐ and AT‐MSCs obtained from normal mice were cultured and labelled. The cells were transplanted to CCL4‐induced ALF mice models intravenously. After cell transplantation, blood samples and liver tissues were collected daily for 72 h to analyze liver enzymes and liver histopathology, respectively. We found that survival rate of AT‐MSC transplanted (AT‐TR) mice was significantly higher than that of control (ALF) group. Liver histopathology was superior in the AT‐TR mice, but not significantly, compared to that in BM‐MSC transplanted (BM‐TR) ones. Furthermore, in the AT‐TR mice the level of aspartate aminotransferase (AST) and alanine aminotransferase (ALT), in some time points were significantly less than those of BM‐TR. Taken together, these data suggest that in comparison to BM‐MSC, AT‐MSCs is an appropriate choice for cell therapy in the case of acute liver failure. Abstract : To the best of our knowledge, this is the first report, comparing the therapeutic potentials of bone marrow‐mesenchymal stem cells (BM‐MSC) with those of adipose tissue (AT‐MSC) in carbon tetrachloride (CCL4)‐induced ALF in mice. Taken together, our data suggest that in comparison to BM‐MSC, AT‐MSCs is an appropriate choice for cell therapy in the case of acute liver failure.